The role of diffusion weighted MR imaging for differentiation between Graves' disease and Hashimoto thyroiditis - Ozturk, T.; Bozgeyik, Z.; Ozturk, F.; Burakgazi, G.; Akyol, M.; Coskun, S.; Ogur, E. (Verduci Publisher, 2015)
OBJECTIVE: The aim of this study was to evaluate the usefulness of diffusion-weighted magnetic resonance imaging (DWMRI) for differentation between Graves' disease and Hashimoto's thyroiditis. PATIENTS AND METHODS: Fifty patients (27 Graves diseases and 23 Hashimoto thyroiditis) and twenty healthy volunteers were examined using T1, T2 and DWMRI. The patients were diagnosed on the basis of physical findings and the results of thyroid function tests and serological tests. Circular ROIs were positioned on the bilateral thyroid lobes and isthmus. All measurements were repeated three different b values including 100, 600 and 1000 s/mm(2) in all cases. ADC (Apparent diffusion coefficient) maps were calculated automatically with the MR system. RESULTS: Mean ADC values were 2.93 x 10(-3), 1.97 x 10(-3) and 1.62 x 10(-3) mm(2)/s in the healthy volunteers; 3.47 x 10(-3), 2.25 x 10(-3) and 1.64 x 10(-3) mm(2)/s in Graves' disease; 2.53 x 10(-3), 1.76 x 10(-3), 1.28 x 10(-3) mm(2)/s in Hashimoto thyroiditis for b100, b600 and b1000, respectively. The ADC values of the Graves diseases were higher than healty volunteers and Hashimoto thyroiditis. ADC values were statistically significant for differentation between Hashimoto thyroiditis and Graves' disease all b values (p < 0.05). dCONCLUSIONS: DWMRI is fast sequence and does not require contrast agent. Quantitative assessment of the lesion is possible using ADC map. So, DWMRI may be useful differentiation of the Hashimoto thyroiditis and Graves' disease.
Keywords: Diffusion weighted magnetic resonance imaging; Grave disease; Hashimoto thyroiditis